Holistic rehabilitation for children with cancer: The Chilean model. Issue 6 (26th July 2021) - Celedón, Vera; Rossell, Nuria; Zubieta, Marcela
Abstract: The increasingly positive outcomes of childhood cancer treatments are among the most inspiring stories in modern medicine. Many of the children and adolescents surviving cancer will have a healthy life; however, many others will suffer from physical, cognitive, psychological, and social sequelae. During treatment, many children experience multiple temporary and permanent side effects which negatively impact their quality of life. Low‐ and middle‐income countries where childhood cancer treatment outcomes are improving are facing the reality of a growing population of teenagers and young adults suffering from long‐term disease‐ and treatment‐related consequences. In Chile, 500 children are diagnosed with cancer each year. Treatment is granted for all through public health policies and NGO collaboration. In order to address the complex problems from acute and long‐term consequences of disease and treatment, the Oncological Rehabilitation Center Fundación Nuestros Hijos (CROFNH) provides multidisciplinary attention to an extensive variety of rehabilitation needs for children and adolescents with cancer. With its integrated services in the medical treatment of children and adolescents with cancer, the CROFNH helps reduce the impact of treatment‐related side effects in children's daily lives, improves quality of life, and aims at contributing to these children becoming independent and functional adults to the maximum of their capacities. The aim of this article is to show the experience of the Chilean Oncological Rehabilitation Centre and its unique multidisciplinary approach. In addition, we discuss the successful telerehabilitation strategy implemented in response to the COVID‐19 pandemic in order to secure continuity of treatment.